POLA HIDUP CERDIK HINDARI KANKER & DETEKSI DINI KANKER PADA PEREMPUAN DI RT 16-18 DESA PENYENGAT OLAK KABUPATEN MUARO JAMBI 2018 - Ajeng Galuh Wuryandari; Indarmien Netty Ariasih; Supatmiyati Supatmiyati (Jurnal Abdimas Kesehatan (JAK), 2019)
The national program for Early Cancer Prevention Movement for Indonesian Women 2015-2019 is being carried out throughout Indonesia. The Indonesian Cancer Foundation (YKI) is a non-profit organization that is working socially and humanitarian in health concern, especially in cancer prevention. YKI has several informative media to help increase the knowledge and awareness of the importance of preventing cancer, one of which is a brochure that contains information about a healthy lifestyle preventing cancer with "CERDIK" ways. It also contains ways to detect cancer early. The target in this community service is Fertile Age Women living in RT 01 to RT 18 Penyengat Olak Village. The purpose of this activity is to increase the women knowledge of childbearing age and awareness of independent cancer early detection. This activity is being carried out by forming a small group of women of childbearing age, giving brochures to fertile-age women groups, and followed by a socialization with question and answer section. This activity is integrated with community service activities for IVA examination. Evaluation of activities shows that there is an increase in knowledge and awareness of independent cancer early detection.